Peran Kegiatan Mewarnai Ember Bekas dan Menanam Kacang Hijau dalam Menumbuhkan Sikap Peduli Lingkungan Anak PAUD : Pendekatan Experiential Learning pada Pendidikan Lingkungan - Putri Suwaibah Safira; Alma Silvi; Dias Amaliah Kangiden; Raja Oloan Tumanggor (Pusat Riset dan Inovasi Nasional, 2025)
Environmental education at an early age is a strategic step to shape children's character who care about the sustainability of nature. This article examines the role of simple but meaningful activities, namely coloring used buckets and planting green beans, in fostering environmental awareness in PAUD children. By using an experiential learning approach, children not only learn through theory, but also experience the recycling and planting process directly as a form of contribution to the environment. This study was conducted through a literature study of relevant literature in the fields of early childhood education, environmental education, and experiential learning approaches. The results of the study show that this activity is able to instill the values of sustainability, responsibility, and social awareness from an early age.